Prevalence and antimicrobial susceptibility of salmonella species isolate from slaughtered cows in Iraq: Arcan A.N. Al-Zubaid and Afaf Abdulrahman Yousif1 - Yousif, Afaf Abdulrahman (The Iraqi Journal of Veterinary Medicine, 2013)
This study was planned to determine the prevalence and antimicrobial susceptibility of Salmonella spp. One hundred bovine with different age and both sexes at slaughterhouse were examined. Four hundred samples were collected from different internal organ (bile, Liver, spleen and mesenteric lymph nodes). Diagnostic study depended upon the morphological and cultural properties of the isolates on some selective media like Brilliant green, XLD, SS agar which used in addition to different biochemical tests, API-20E )Enterobacteriaceae Identification Kit.). Isolates were serotyped at the Central Public Health Laboratories (National Center of Salmonellae in Baghdad, Iraq). Eleven isolates consisting of Salmonella anatum (9.09%), S.newport (27.27%), S.enteritidis (45.45 %) and S.ohio (18.18%). The percentage of infection were 3% in the mesenteric lymph node and liver, (4%) in bile, and (1%) in spleen. The antibiotic susceptibility pattern of Salmonella against 15 antimicrobial drugs revealed that all isolates were sensitive (100%) to ciprofloxacin and amicacin. And most of isolates were resistance to cloxacillin, cefixime, amoxicillin. and gave intermediate results to neomycin, gentamycin, tetracycline and streptomycin.